Enhancement‐Mode β‐Ga2O3 Metal‐Oxide‐Semiconductor Field‐Effect Transistor with High Breakdown Voltage over 3000 V Realized by Oxygen Annealing. Issue 3 (22nd December 2019) - Lv, Yuanjie; Zhou, Xingye; Long, Shibing; Wang, Yuangang; Song, Xubo; Zhou, Xuanze; Xu, Guangwei; Liang, Shixiong; Feng, Zhihong; Cai, Shujun; Fu, Xingchang; Pu, Aimin; et al.
Abstract : Herein, high‐performance enhancement‐mode (E‐mode) β ‐Ga2 O3 metal‐oxide‐semiconductor field‐effect transistors (MOSFETs) are achieved on Si‐doped homoepitaxial films. Oxygen annealing (OA) treatment under the gate region is used to effectively exhaust the channel electron, resulting in the normally off operation of the device. The threshold voltage, defined as that at the drain current of 0.1 mA mm −1, for the fabricated device is extracted to be 4.1 V. Moreover, double source‐connected field plates are used to suppress the peak electric fields in both Ga2 O3 channel and SiN x passivation layer. The fabricated β ‐Ga2 O3 MOSFETs with gate‐to‐drain distance ( L gd ) of 17 μm exhibit a record high breakdown voltage over 3000 V. It is shown that the OA treatment is a new way to obtain high‐performance E‐mode β ‐Ga2 O3 power MOSFETs. Abstract : Gallium oxide (Ga2 O3 ) has great potential in high‐power and low‐loss devices. Enhancement‐mode (E‐mode) epitaxy‐ β ‐Ga2 O3 metal‐oxide‐semiconductor field‐effect transistors (MOSFETs) with large threshold voltages of 4.1 V are achieved by oxygen annealing (OA) in the gated region. The device achieves a record breakdown voltage over 3000 V using double source‐connected field plates. The OA treatment shows a new way to obtain E‐mode β ‐Ga2 O3 MOSFETs.